You defend what you feel: 'Presencing' nature as 'experiential knowing'. Issue 1 (March 2019) - Gioacchino, Gioel
This article reflects on a youth-led action research process on climate change adaptation carried out in Cuba between 2013 and 2015. The research explored the question: 'How are Cuban youth engaging with climate change adaptation challenges and what can we learn from it?'. The objectives of the research were to understand young people's attitudes towards climate change and environmental work while connecting a youth network in Cuba and encourage collaboration. This article contributes to PAR with a rich description of a research process in which the group of co-researchers was able to collectively shift their awareness of and personal relationship with nature. Proposing a conversation between Heron and Reason's extended epistemology (1997) and Scharmer's TheoryU (2016, 2018), I argue that experiential knowledge in climate change and environmental work looks like entering an intimate state of co-presencing with the aliveness of the earth. Second of all, the research contributes to the literature on youth participation highlighting that in Cuba there is a gap between the political will and attention towards climate change adaptation, which is remarkable, and young people's ability to meaningfully take leadership in such efforts.